Pemaknaan Kiamat dalam Penafsiran Umar Sulaiman Abdullah Al-Asyqar (TAFSE: Journal of Qur'anic Studies, 2019)
In the Qur'an there are many verses that talk about the apocalypse, there are also various interpretations produced by the interpreters. This paper wants to examine the interpretation and understanding of Umar Sulaiman al-Asyqar regarding the doomsday verse, this may be different from other commentators because of the different methods and characteristics of interpretation. This research is a bibliographical study with the data sources being the books of al-Ma'ānī al-Ḥasān fī Tafsīr al-Qur'ān and al-'Aqīdah fi 'i al-Kitāb wa al-Sunnah: al-Qiyāmah al-Kubra. Data was collected through thematic methods), and the analysis was carried out descriptively. The results of the study indicate that Umar Sulaiman interprets the word tafjīr as having the same meaning (synonym) as the word tasjīr which means burning (انفجار) or exploding (انسجار), while previous commentators distinguish the word tafjīr which means mixed up (إختلاط) with the word tasjīr which means lit (إضطرام). Dalam al-Qur’an terdapat banyak ayat yang berbicara mengenai kiamat, terdapat beragam pula penafsiran yang dihasilkan oleh para penafsir. Tulisan ini ingin mengkaji penafsiran dan pemahaman Umar Sulaiman al-Asyqar mengenai ayat kiamat, hal ini berkemungkinan berbeda dengan mufasir lainnya karena metode dan karakteristik penafsiran yang berbeda. Penelitian ini bersifat kepustakaan dengan sumber data kitab al-Ma‘ānī al-Ḥasān fī Tafsīr al-Qur‘ān dan al-‘Aqīdah fi Ḍū’i al-Kitāb wa al-Sunnah: al-Qiyāmah al-Kubra. Pengumpulkan data dilakukan melalui metode tematik), dan analisi dilakukan secara deskriptif. Hasil dari penelitian menunjukkan bahwa Umar Sulaiman menafsirkan kata tafjīr  mempunyai persamaan makna (sinonim) dengan kata tasjīr yang diartikan menyala (انفجار) atau meledak (انسجار), sedangkan mufasir terdahulu membedakan kata tafjīr yang diartikan bercampur baur (إختلاط) dengan kata tasjīr yang diartikan menyala (إضطرام).
Keywords: Penafsiaran; Kiamat; Tematik